ANALISIS KESALAHAN LOKAL DAN GLOBAL DALAM MENULIS SURAT PRIBADI SISWA KELAS XI SMA NEGERI 1 TAMAN - HELENA NGURA, PERPETUA (LATERNE, 2016)
Writing is one of language skills which must be mastered in particular students in German essays writing. The background of this research is students in class XI language of SMA Negeri 1 Taman still encounter difficulties in letter writing and not yet fully understood the rules of Germans writing. The students has not mastered the Germans grammar and rules of writing in sentence. Students still misplaced verbs, articles, prepositions, and has not mastered the rules of writing nouns in German. Therefore, perform the error analysis in students essay. This study aims to determine any erorrs, both global and local error that appears on the letter written by the students of SMA Negeri 1 Taman. The problemm of this research is what type of error that appear in students  letter. This study is a qualitative study with descriptive analysis method, which aims to define or describe objectively according the purpose of writing. The data were collected and then classified and analyzed based on the type of error. On the results of the analysis found several errors. They are global error and local error. When compared with global error, the error that most appear is local error caused by writing uppercase and lowercase error. Almost all student make the similar mistake. These errors can be caused bacause the students did not know the rules of grammar and writing in German language. With the research teacher must giving more information about Germans grammar and rules of writing. In addition, teachers also give often more writing exercise to the students, so can reducing the possibility for them making the similar mistakes. Keywords : analysis of error, global error, local error